DOI: 10.14264/uql.2017.49
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the deleterious effect of clay minerals on copper flotation

Abstract: Clay minerals have a deleterious effect on the mineral flotation process. Generally, two major phenomena are observed in industry when processing high clay ores: no froth formed on the top of the pulp phase and few valuable minerals loaded on the top of froth. This is an ARC Linkage project with support from Pionera, a reagent company manufacturing biopolymers.The objective of the project is to define the different effects of clay minerals on copper flotation, and then to mitigate the deleterious effects of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…Recently, some researchers have used natural polymers to modify the rheology of flotation slurries with clay contents, and in all studies, rheograms were produced to analyze the effect of rheology modifiers. Wei et al used 100 g/t of the dispersant F‐100, a lignosulphonate‐based polymer, to improve copper and gold flotation from a high clay ore, and it was observed that when using stainless steel grinding media, the effect of the dispersant on rheology was not as significant as the increase in copper and gold recovery.…”
Section: Rheology In Mineral Processing Unit Operationsmentioning
confidence: 99%
“…Recently, some researchers have used natural polymers to modify the rheology of flotation slurries with clay contents, and in all studies, rheograms were produced to analyze the effect of rheology modifiers. Wei et al used 100 g/t of the dispersant F‐100, a lignosulphonate‐based polymer, to improve copper and gold flotation from a high clay ore, and it was observed that when using stainless steel grinding media, the effect of the dispersant on rheology was not as significant as the increase in copper and gold recovery.…”
Section: Rheology In Mineral Processing Unit Operationsmentioning
confidence: 99%
“…Clay minerals are all fundamentally built of tetrahedral (T) sheets and octahedral (O) sheets that are bonded in certain proportions with various forces and atoms to form clay macrostructure (Brigatti et al 2013). Based on the layer structures and bonding forces of layers, the most commonly occurring clay minerals in ore deposits can be classified into three groups: kaolin, smectite, and illite (Cruz 2016;Wang 2016;Zhang 2016). The structure representative of a mineral in each group is shown in Figure 1.…”
Section: Classification and Structures Of Clay Mineralsmentioning
confidence: 99%
“…1,2 Phyllosilicates are comprised of layered silica tetrahedral sheets and alumina or magnesia octahedral sheets in varying proportions. [3][4][5][6] They can adhere to the surfaces of target minerals during otation, changing froth stability and rheology and thereby reducing the grade and recovery of valuable minerals. 7,8 Physical and chemical strategies to counteract the negative effects of phyllosilicate clays have led to overconsumption of some dispersants and depressants, lower pulp solid concentrations, high water consumption, and the need for intense agitation prior to otation to lower viscosities.…”
Section: Introductionmentioning
confidence: 99%